27. SOME CLINICAL CHARACTERISTICS OF PATIENTS WHO TREATED CLOSED DISTAL CLAVICLE FRACTURE BY PRECONTOURED LOCKING PLATE AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2024)
Objective: Survey of some clinical characteristics of patients with closed distal clavicle fracture, treated by precontoured lateral clavicle locking plate.Subject and method: A descriptive research at Military Hospital 175 from January 2022 to May 2024 on 35 adult patients with closed distal clavicle fracture, treated by osteosynthesis with precontoured lateral clavicle locking plate method.Results: The average age of the study group was 41.66 ± 15.21 years old (ranged from 17 to 68 years old). The male/female ratio is 1.69/1. The cause of distal clavicle fracture due to traffic accidents accounts for the highest rate with 94.28%, daily life accidents and work accidents account for 2.86%. There were 14/35 cases of trauma that involved both distal clavicle fracture and damage to other positions.Conclusion: This shows that fractures of distal clavicle are often accompanied by injuries to other organs with varying degrees of severity depending on the impact force caused by the injury. Therefore, when examining, it is necessary to be very careful in taking medical history to avoid missing injuries.
Keywords: Upper limb; distal clavicle; clinical characteristic